Proliferative and viability effects of two cyanophages on freshwater bloom-forming species Microcystis aeruginosa and Raphidiopsis raciborskii vary between strains - Nada Tokodi; Antonia Łobodzińska; Barbara Klimczak; Adam Antosiak; Sara Młynarska; Sigitas Šulčius; Sarit Avrani; Takashi Yoshida; Dariusz Dziga (Scientific Reports)
Abstract Viruses that infect cyanobacteria are an integral part of aquatic food webs, influencing nutrient cycling and ecosystem health. However, the significance of virus host range, replication efficiency, and host compatibility on cyanobacterial dynamics, growth, and toxicity remains poorly understood. In this study, we examined the effects of cyanophage additions on the dynamics and activity of optimal, sub-optimal, and non-permissive cyanobacterial hosts in cultures of Microcystis aeruginosa and Raphidiopsis raciborskii. Our findings reveal that cross-infectivity can substantially reduce the proliferative success of the cyanophage under conditions of high-density of sub-optimal hosts which suggests phage dispersal limitation as a result of shared infections, in turn impairing their top-down control over the host community. Furthermore, we found that cyanophage addition triggers host strain-specific responses in photosynthetic performance, population size and toxin production, even among non-permissive hosts. These non-lytic effects suggest indirect impacts on co-existing cyanobacteria, increasing the overall complexity and variance in many ecologically relevant cyanobacterial traits. The high variability in responses observed with a limited subset of cyanophage-cyanobacteria combinations not only highlights the intricate role of viral infections in microbial ecosystems but also underscores the significant challenges in predicting the composition, toxicity, and dynamics of cyanobacterial blooms.